The Empirical Study on Digital Literacy from the Viewpoint of Digital Accessibility - Joon Sung, Wook (International Journal of Engineering and Technology, 2018)
The purpose of this study is to empirically analyze the effect of motivation factor in digital literacy. In particular, we examine the cumulative and recursive model of digital access, and examine the causal path of motivation factor to digital usages by analyzing the effects of motivation access on material access, skill access, and usage access. For the analysis, we used ‘the digital divide index and actual survey’ data of National Information Society Agency (NIA). The analytical model used the structural equation, and the statistics program used SPSS 23 and Amos 23. The results show that the motivation factor for digital literacy has a significant effect on material access, skill access and usage access. Policies that take into account motivations factors in digital literacy need to be strengthened.